Exploring the Potential of Waste Cooking Oil in Enhancing Warm Mix Asphalt Performance - Hamzah, Ahmad Mujahid; Mior Sani, Wan Noor Hin; Mawardi, Indra; Yacoob, Haryati; Rogo, Kabiru Usman; Hashim, Mohd Hazree (Popular Scientist, 2025)
The growing need for sustainable materials in road construction has led to the investigation of waste cooking oil (WCO) as a modifier for warm mix asphalt (WMA). This study evaluates the effects of chemically treated WCO on the mechanical properties of WMA, focusing on stability, resilient modulus, and dynamic creep performance. WCO was treated through transesterification and incorporated into 60/70 penetration grade asphalt at various dosages (0%, 3%, 4%, and 5% by weight of asphalt). The results showed that a 3% WCO-modified asphalt achieved the highest stability and acceptable resilient modulus, while maintaining satisfactory rutting resistance. Higher WCO content led to reduced stiffness and creep performance due to excessive softening. The study concludes that treated WCO can enhance WMA performance when used in optimal amounts, contributing to sustainable pavement practices.